Organic compost addition to raw rice husk substrate for tomato (Solanum lycopersicum) hybrid variety cultivation in a leach recirculating system - Carini, Fernanda; Nogueira Peil, Roberta Marins; Marques, Gabriel Nachtigal; Grolli, Paulo Roberto; Souza, Rafaela Schmidt De (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 94-103).